Self-monitoring of blood glucose (SMBG) and glycaemic control in Cameroon: Results of the International Diabetes Management Practices Study (IDMPS) - Claude Mbanya, Jean (2017)
This study examined the relationship between self-monitoring of blood glucose (SMBG) and glycaemic control among patients from Cameroon. A minority of patients with diabetes owned a blood glucose meter; of these patients, most performed SMBG inconsistently. The lack of SMBG may be a contributing factor to the poor glycaemic control in the country.